2012
DOI: 10.1124/mol.112.079855
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Protects Soluble Guanylate Cyclase against Oxidative Inactivation

Abstract: Tetrahydrobiopterin (BH4) is a major endogenous vasoprotective agent that improves endothelial function by increasing nitric oxide (NO) synthesis and scavenging of superoxide and peroxynitrite. Therefore, administration of BH4 is considered a promising therapy for cardiovascular diseases associated with endothelial dysfunction and oxidative stress. Here we report on a novel function of BH4 that might contribute to the beneficial vascular effects of the pteridine. . Whereas scavenging of superoxide and/or perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Oral SP inhibited expression of inflammatory cytokines (IL-1β, IL-6, IL-17A), reduced infiltration of inflammatory cells (neutrophils and macrophages), and significantly inhibited the increased protein Tyr nitration in the diseased colons. These results are consistent with DSS/chronic inflammation induced uncoupling of NOS although we could not eliminate that BH4 or SP also protect sGC from oxidative inactivation (20). …”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Oral SP inhibited expression of inflammatory cytokines (IL-1β, IL-6, IL-17A), reduced infiltration of inflammatory cells (neutrophils and macrophages), and significantly inhibited the increased protein Tyr nitration in the diseased colons. These results are consistent with DSS/chronic inflammation induced uncoupling of NOS although we could not eliminate that BH4 or SP also protect sGC from oxidative inactivation (20). …”
Section: Introductionsupporting
confidence: 77%
“…SP is an antioxidant and shown to possibly protect sGC from oxidant-inactivation (20). To rule out this role in the cytotoxic activity of SP, cells were incubated with, tetrahydroneopterin (NHP4), a biopterin with equivalent free radical scavenging activity as SP but unable to participate as a cofactor for NOS (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BAY60) can stimulate sGC cyclase activity independent of NO or heme; oxidized sGC has a relatively potentiated response to sGC activators [24]. Thus, differential cyclase response of sGC to BAY60 versus NO-donor DEA/NO can reveal its redox state [48]. We previously showed that while NLR-localized sGC becomes oxidized in the volume-overloaded heart, caveolae-localized sGC does not [29].…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular levels of pteridines were quantified by HPLC analysis using a method adapted from Fukushima and Nixon [20] as described previously [21]. Briefly, cells grown in petri dishes (diameter 90 mm) were harvested (∼5 × 10 6 per petri dish), washed, and resuspended in either 0.1 ml of PBS containing 1 mM DTT (for quantifying biopterin), 0.1 ml of alkaline oxidant solution (0.02 M KI/I 2 in 0.1 M NaOH; for quantifying biopterin plus BH2), or 0.1 ml of acidic oxidant solution (0.02 M KI/I 2 in 0.1 M HCl; for quantifying biopterin plus BH2 plus BH4).…”
Section: Methodsmentioning
confidence: 99%